ANALISA PENYEBAB KEAUSAN POROS BALING BALING KAPAL - Andi Hendrawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2019)
Ship propellers are very important because in general ships moving in the medium of water with a certain speed, it will experience a drag (resistance) that isopposite to the direction of motion of the ship. The amount of drag that occurs must be able to be overcome by the thrust of the ship (thrust) resulting from thework of the ship's propulsion. Other causes of bale blast wear: Breaking of propeller shaft seal, Propeller shaft lubricating oil circulation is not smooth,Unbalanced propeller shaft, so to prevent damage is needed periodic maintenance and repair so that the propeller shaft can work optimally.